Robotic device for transcranial focussed ultrasound applications in small animal models - Antoniou, Anastasia; Giannakou, Marinos; Georgiou, Elena; Kleopa, Kleopas A.; Damianou, Christakis A. (My University, 2022)
Abstract Background: Focussed Ultrasound (FUS) combined with microbubbles (MBs) was proven a promising modality for non‐invasive blood brain barrier disruption (BBBD). Herein, two devices for FUS‐mediated BBBD in rodents are presented. Methods: A two‐axes robotic device was manufactured for navigating a single element FUS transducer of 1 MHz relative to the brain of rodents. A second more compact device featuring a single motorized vertical axis was also developed. Their performance was assessed in terms of motion accuracy, MRI compatibility and trans‐skull BBBD in wild type mice using MBs in synergy with pulsed FUS. Results: Successful BBBD was evidenced by the Evans Blue dye method, as well as by Fibronectin and Fibrinogen immunostaining. BBB permeability was enhanced when the applied acoustic intensity was increased. Conclusions: The proposed devices constitute a cost‐effective and ergonomic solution for FUS‐mediated BBBD in small animal models. Further experimentation is needed to examine the repeatability of results and optimise the therapeutic protocol.
Keywords: robotic device; transcranial; BBB disruption; focussed ultrasound; mice; MRI compatible